2003
DOI: 10.3201/eid0906.030017
|View full text |Cite
|
Sign up to set email alerts
|

Human Metapneumovirus Infections in Hospitalized Children1

Abstract: We evaluated the percentage of hospitalizations for acute respiratory tract infections in children < 3 years of age attributable to human metapneumovirus (HMPV) and other respiratory viruses in a prospective study during winter and spring 2002. We used real-time polymerase chain assays and other conventional diagnostic methods to detect HMPV, human respiratory syncytial virus (HRSV), and influenza viruses in nasopharyngeal aspirates of children. HMPV was detected in 12 (6%) of the 208 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
201
10
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 388 publications
(245 citation statements)
references
References 16 publications
20
201
10
14
Order By: Relevance
“…Proportions of hMPV-infected patients with chronic underlying diseases (30% versus 29%) and a history of prematurity (11% versus 21%) were comparable in both study phases and also similar to previous observations [5,12,30,32]. These rates are high compared to the normal population and either indicate an increased susceptibility for infection or a bias towards a greater likelihood for diagnostic tests in these high-risk patients.…”
Section: Discussionsupporting
confidence: 86%
“…Proportions of hMPV-infected patients with chronic underlying diseases (30% versus 29%) and a history of prematurity (11% versus 21%) were comparable in both study phases and also similar to previous observations [5,12,30,32]. These rates are high compared to the normal population and either indicate an increased susceptibility for infection or a bias towards a greater likelihood for diagnostic tests in these high-risk patients.…”
Section: Discussionsupporting
confidence: 86%
“…In some reports, none of the children infected with hMPV required ICU admission (28); however, others indicated that 15-25% of children required ICU care (31). Moreover, in the present work, there were no deaths associated with hMPV infection.…”
Section: Discussioncontrasting
confidence: 37%
“…In this study, prematurity was found in one patient and co-morbidities were noticed in two patients, including cardiac disorder in one patient (25%) and allergy in the other one (25%). Similarly, Boivin et al (28) found that 25% of children with hMPV infection had a cardiac disorder. Hence, the determination of risk factors for severe hMPV disease in young children can identify high-risk groups, who would benefit from preventive and therapeutic strategies (29).…”
Section: Discussionmentioning
confidence: 88%
“…Adenoviruses 1, 2, and 5 have been isolated from infants with pharyngitis and coryza or who have otherwise been asymptomatic, and children exhibit a wide variety of clinically apparent respiratory syndromes associated with tonsils and adenoids, 18,34,51,70 upper respiratory disease, 18,34,51,61,70 intussception, 18,51,61,70 and pharyngoconjunctival fever. 46,83 Serotypes 3, 4, and 7 are common etiologies of acute viral respiratory disease in young adults, with serotype 4 often associated with epidemic infections in closed populations such as military recruits and types 5, 31, and 34 responsible for viral pneumonia with concomitant dissemination in immunocompromised patients.…”
Section: Viral Respiratory Diseases Orthomyxoviridaementioning
confidence: 99%
“…48,82 Whereas Respiratory syncytial virus tends to be severe in infants, with most children exhibiting seroevidence of infection by age 2 years, only 50% of children have metapneumovirus antibodies by 2 years, eventually reaching 100% seroprevalence by age 5. [83][84][85] They are typical paramyxoviruses with a negative sense, ssRNA, helical nucleocapsid, and a pleomorphic outer lipid envelope with peplomers projecting from the surface. 86 These surface projections are the F (fusion) protein, which permit viruses to enter host cells, release progeny, and infect adjacent cells, leading to characteristic syncytia.…”
Section: Viral Respiratory Diseases Orthomyxoviridaementioning
confidence: 99%